Dithieno(3,2-b:2′,3′-d)phospholes: a look back at the first decade - Romero-Nieto, Carlos; Baumgartner, Thomas (Synlett, 2013)
In this account, we describe our efforts in developing the chemistry of the highly luminescent dithieno[3,2-b:2′,3′-d]phosphole system over the last ten years. We provide an overview of the synthetic possibilities and the inherent tunability of the emission properties offered by this particular heterole. 1 Introduction 2 Synthesis and Properties of Dithieno[3,2-b:2′,3′-d]phospholes 3 Functionalization of Dithieno[3,2-b:2′,3′-d]phospholes 3.1 Phosphorus Functionalization 3.2 Functionalization at the 2- and 6-Positions 3.2.1 Symmetric Functionalization 3.2.2 Asymmetric Functionalization 3.3 Incorporation of Fused Rings onto the Main Scaffold 4 Photophysical Properties 5 Conclusions